Estudo da comunidade bacteriana associada a Podocarpus macrophyllus: interações na microbiota, compostos fixos e voláteis, e do potencial de aplicação na biotecnologia - Pereira, Thieres Magaive Costa (2019)
The diversity of the bacterial community associated with the Podocarpus Macrophyllus plant has been systematically studied in order to determine the genera of bacteria that are commonly associated with this plant, as well as the composition of the community bacterial changes due to regional and seasonal conditions. It was included that genus Bacillus is the main associated with the host plant, being isolated in all regions and seasons, and in all tissues used in the procedures of isolation. Within this genus, the species Bacillus pumilus was largely isolated in all studied conditions. Additionally, the biotechnological potential of the main bacteria associated with the plant was evaluated by the studying the production of fixed and volatile compounds, as well as the interaction with endophytic fungi associated with the same plant. These bacteria are skillful producing lipopeptides, surfactin and iturin were identified and isolated from all strains, fengycins were isolated from LaBioMMi 1180 and 1202 strains that correspond to Bacillus subtilis. Finally, the plantazolicin was isolated from LaBioMMi 1137, which corresponds to Bacillus pumilus, and such metabolites are the main responsible for the inhibitory activity of these bactéria, when cultivated with endophytic fungi Isolated from the same plant. With regard to volatile compounds, all strains demonstrate great ability to produce nitrogenous compounds, such as pyrazine, and oxygenated compounds as short chain ketones. Bacillus spp. demonstrates great potential for biotechnological application for bioremmenation and biodegradation of polymers. When cultivated in medium enriched with Fe3+, LaBioMMi 1141 demonstrated the ability to absorve much of the heavy metal content depending on the condition in which it was cultivated. The results for the biosorption of Cu2+ and the composition of Fe3+ together with Cu2+ showed no satisfactory results in comparison with Fe3+ alone. On the other hand, LaBioMMi 1180 has been shown to be able to degradate several polymers, when these are the unique carbon source in the medium, thus demonstrating the great potential of these endophytic microorganisms.